Clostridium butyricum Supplement Can Ameliorate the Intestinal Barrier Roles in Broiler Chickens Experimentally Infected With Clostridium perfringens - Xu, Xiao; Yang, Shunli; Olajide, Joshua Seun; Qu, Zigang; Gong, Zhenxing; Wang, Jing; Zhang, Yanbing; Wang, Heng; Xiong, Ling; Zhang, Kun; Zhou, Enmin; Cai, Jianping (Frontiers in Physiology, 2021)
Necrotic enteritis (NE), which is caused by Clostridium perfringens (C. perfringens), is an economically important disease in the broiler. Among normal flora in the broiler intestinal, Clostridium butyricum (C. butyricum) has been identified as a probiotic agent that reduces the susceptibility of broilers to C. perfringens. However, the effects of C. butyricum infection on broiler intestinal integrity during NE are largely unknown. In this study, we investigated the effects of C. butyricum on the growth performance, intestinal morphology, and barrier function, as well as the functions of immune-related cytokines under NE in broilers. Chickens were divided into five groups: control group (NC), supplement C. butyricum only (CB) and NE infected group (PC) with supplement C. butyricum at different days (NECB1 and NECB2). The results showed that the infected group (PC) decrease significantly in the average daily gain and an increase in feed conversion ratio compared with C. butyricum through a dietary supplement. From Hematoxylin-Eosin staining jejunum sets we could know that supplementation of C. butyricum (NECB1 and NECB2) restored the intestinal villus height, increased the crypt depth, and reduced the intestinal damage under NE. Elisa and Limulus Test found that broilers infected with NE had higher serum IgA and lipopolysaccharide content, and after addition with C. butyricum (NECB1 and NECB2) returned to a normal level. In addition, real-time PCR and western blot results showed that compared with PC, supplementation of C. butyricum (NECB1 and NECB2) restored intestinal barrier function-related genes (such as CLDN-1, CLDN-3, OCLN, MUC2, ZO-1, and CLDN5), cytokines (such as TNF-, IL-10, IL-6, and TGFB1) and C. perfringens plc gene expression. Moreover, the results detected by Ussing chamber suggested that C. butyricum (NECB1 and NECB2) could restore the decrease in conductivity value and short-circuit current value caused by NE (PC). Furthermore, NECB2 reduced the upregulation of fluorescein isothiocyanate-dextran flux caused by NE infection. In general, these findings evidence that dietary supplementation of C. butyricum into broilers with NE improved chicken growth performance, intestinal morphology, intestinal barrier function, and immune function. Notably, no statistical difference was observed with the addition of C. butyricum on day 1 or day 14.